Diagnóstico comunitario de salud del Barrio Labanda bajo sector III y IV, septiembre-diciembre de 2013 - Peña Carrión, Yessica Amparo (2013)
The present investigation has as main objective to Contribute the invigoration of the PATTERN OF INTEGRAL ATTENTION OF THE COMMUNITY NATIONAL SYSTEM OF FAMILY HEALTH AND INTERCULTURAL in the University Hospital of Motupe, contributing with statistical and data that will allow to the Basic Teams of Health - EAIS (Teams of Integral Attention of Health) to formulate local proposals of health, spread to improve the quality of life of the community of La Banda Bajo Sector III y IV. The universe was constituted by 59 families and 230 inhabitants, the present investigation is of descriptive type, in which facts and characteristic related with the population and its environment are detailed, the instrument for the gathering of information was the family record elaborated by MSP and an annex to this record, the interview form allowed to complete the information, it was also analyzed the data, obtaining results that they will serve as base line. Among the most outstanding data we highlight; that the sex more prevalent is the feminine one, the level of more excellent education it is the Basic one, he/she was 8 Illiterates of which some are heads of household, as soon as school and adolescents great part of them this with nutritional good state and most studies, in what concerns women with sexual active life, the method of the rhythm is the more used for the family planning. As for the epidemic profile we highlight that the Hypertension is the chronic pathology that more prevails affecting to ages understood between the 20 and 64 years, among the degenerative illnesses, and what concerns to discapacities the most excellent is the intellectual discapacity. The investigation is supported with bibliography and annexes that it contemplates the development of the same one. Keywords: Community health diagnostic, model of integrated health care